Answer:
3 ft, 4 ft
Step-by-step explanation:
Represent the length of the shortest leg using x. Then the other leg length is x + 1. Applying the Pythagorean Theorem,
x^2 + (x + 1)^2 = 5^2, or
x^2 + x^2 + 2x + 1 = 25, or
2x^2 + 2x - 24 = 0.
Reducing this, we get x^2 + x - 12 = 0, or (x + 4)(x - 3) =0.
Solving for x: x + 4 = 0 => x = -4; also x - 3 = 0 => x = 3
Since we're measuring length, let's omit x = -4 and focus on x = 3.
Shortest leg is 3 ft long; other leg length is 3 + 1 ft, or 4 ft, long.